Toponimi Nama-Nama Tempat di Kecamatan Kuta dan Kuta Selatan Kabupaten Badung Bali - Pradyani, Kadek Endina; Suryati, Ni Made; Suteja, I Wayan (Humanis; Vol 27 No 1 (2023)DO - 10.24843/JH.2023.v27.i01.p05, 2023)
The results of this study are to describe the toponyms found in the origins of place names in Kuta and South Kuta Districts. The use of toponymy theory in this analysis is able to reveal toponymy aspects of place names in Kuta and South Kuta Districts.   Based on the toponymy theory according to Robiansyah (2017: 13), it is grouped into four, namely (1) vegetation toponymy; (2) historical toponymy; (3) toponymy of gifts; (4) regional toponymy in place names in Kuta and South Kuta Districts. The methods and techniques used consist of three stages, namely: (1) The stage of providing data using the listening method, followed by the technique of observing the skilled engagement (SLC) technique, and the recording technique, as well as the proficient method, followed by the fishing technique and the proficient technique, ( 2) The data analysis phase uses the matching method with the advanced technique of selecting determinant elements (PUP) and the comparative comparison technique (HBB), as well as the distribution method with the advanced technique of dividing the direct elements (BUL), (3) The data analysis results stage uses the method formal and informal methods supported by deductive and inductive techniques. The toponymic aspects of place names in Kuta and South Kuta sub-districts include four types of toponymy, namely vegetation toponymy, historical toponymy, gift toponymy, and area toponymy which is the origin of the place names.